Sudden death in hypertrophic cardiomyopathy: associated accessory atrioventricular pathways. - Krikler, D M (1980)
Sudden death is a known but unpredictable complication of hypertrophic cardiomyopathy. We describe two patients who both had a strong family history of the disorder complicated by sudden death. Necropsy disclosed accessory bypass tracts, concealed in one and previously suspected in the other. One died from ventricular fibrillation and the other, who died outside hospital, had previously complained of palpitation. Arrhythmia complicating pre-excitation appears to be one of the factors responsible for sudden death in hypertrophic cardiomyopathy.